2010
DOI: 10.1111/j.1600-0633.2010.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Microgeographic genetic isolation in chub (Cyprinidae: Squalius cephalus) population of the Durance River: estimating fragmentation by dams

Abstract: Weirs and dams are wide spread throughout the world's river systems. The most direct effect of these barriers is the limitation of organism movements, i.e., the alteration of connectivity by fragmentation of the aquatic habitat. Whereas the impact of fragmentation on migratory fish species has been well studied, insights on nonmigratory species are still needed. In particular, knowledge on the effects of dams on cyprinid populations at the watershed scale is lacking. Therefore, we studied the genetic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 59 publications
5
32
0
Order By: Relevance
“…Although these areas are vulnerable to bottlenecking, the same signal is compatible with a scenario of re-colonisation post-extirpation (Hänfling and Weetman 2006). IBD is expected in riverine freshwater fishes but it is not universally found in all river populations (Hänfling et al 2004;Dehais et al 2010;Hamilton et al 2014), corroborating our findings. The strength of IBD may also vary over generations, complicating biological interpretation of snapshot estimates (Junge et al 2011).…”
Section: Drivers Of Genetic Differentiation and Population Connectivitysupporting
confidence: 90%
See 2 more Smart Citations
“…Although these areas are vulnerable to bottlenecking, the same signal is compatible with a scenario of re-colonisation post-extirpation (Hänfling and Weetman 2006). IBD is expected in riverine freshwater fishes but it is not universally found in all river populations (Hänfling et al 2004;Dehais et al 2010;Hamilton et al 2014), corroborating our findings. The strength of IBD may also vary over generations, complicating biological interpretation of snapshot estimates (Junge et al 2011).…”
Section: Drivers Of Genetic Differentiation and Population Connectivitysupporting
confidence: 90%
“…2) and are consonant with estimates observed in this species in the UK, exhibiting significant overlap between mean and variances in heterozygosity and allelic richness across all surveyed Thames sub-populations (Hamilton et al 2014). Concordance of diversities is also to be found in European roach (Demandt 2010) and in European coarse fish generally (e.g., Dehais et al 2010). Each microsatellite locus shows a similar statistical distribution of allele frequencies in either river (Fig S1).…”
Section: Genetic Diversitysupporting
confidence: 79%
See 1 more Smart Citation
“…Dams and Hydroelectric Power Plants (HPP) do not to allow WPs of migratory fish to pass upstream to reach their reproduction locations (DEHAIS et al, 2010). The study by Makrakis et al (2007Makrakis et al ( ) from 1997Makrakis et al ( to 2005 in the Paraná River Basin in Brazil, Paraguay and Argentina observed a migratory path for Piaractus mesopotamicus stretching up to 422 km (26.4 km/day).…”
Section: Genetic Variabilitymentioning
confidence: 99%
“…Cyprinid species are found in a number of different geographic regions and habitat types, and populations face many threats to their persistence including habitat fragmentation (Alo and Turner 2005;Skalski et al 2008;Dehais et al 2010), alterations in the natural hydrologic regime (Platania 1991;Scheerer 2002), conversion of habitat to agricultural and urban areas (Waite and Carpenter 2000), and introductions of nonnative species that compete with and prey upon native cyprinids (Platania 1991;Simon and Markle 1999;Matthews and Marsh-Matthews 2007). As a result of these threats, many cyprinid species are presently threatened, endangered, or declining in abundance.…”
mentioning
confidence: 99%